Degradable polyurethane film and preparation method thereof

Through the composite materials of polyurethane, hydroxyethyl starch, methylcellulose and other components, as well as hydrophobic coating and freeze-thawing processes, the problem of incompatibility of the mechanical properties and degradation properties of the coating film is solved, and a high-strength, moisture-resisting and controllable degradation polyurethane film is achieved.

CN120399430APending Publication Date: 2025-08-01NANJING 3H MEDICAL PROD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510704870.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-29
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing degradable coating films are incompatible with the mechanical properties and degradation properties, and have poor humidity resistance, making it difficult to meet the needs of packaging materials.

Method used

A composite material of polyurethane, hydroxyethyl starch, methyl cellulose, tributyl citrate and other components is used to combine hydrophobic coating and freeze-thawing process to form a porous structure to enhance the tensile strength and moisture resistance of the material.

Benefits of technology

The tensile strength is improved to 10MPa, and the moisture resistance is improved several times, achieving controllable degradation performance, meeting the mechanical and environmental adaptability needs of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399430A_ABST
    Figure CN120399430A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable polyurethane film and a preparation method thereof. The polyurethane film is prepared from the following components in parts by mass: 7.5 to 11 parts of polyurethane, 78 to 85 parts of water, 2.4 to 4.5 parts of hydroxyethyl starch, 1.3 to 2.5 parts of methyl cellulose, 16 to 3.2 parts of acetyl tributyl citrate, 0.85 to 1.3 parts of plasticizer, 0.1 to 0.16 part of cross-linking agent and 0.5 to 1.6 parts of reinforcing agent. According to the invention, polyurethane is used as a matrix, hydroxyethyl starch and methyl cellulose are cooperatively modified, repeated freezing and thawing are carried out, and a coating film-forming process is adopted to prepare the coating film. By regulating and controlling the compounding ratio and the cross-linked network structure of the material, the balance of high mechanical strength (the tensile strength is greater than or equal to 10MPa) and rapid degradation performance (the weight loss ratio is greater than 90% within 60 days in a natural environment) is realized, and the functional expansion in environmental monitoring is realized. Compared with a traditional PE film, the product has the advantages of degradability, barrier property and cost, is suitable for the fields of medical packaging and the like, and has remarkable environmental protection value and industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a degradable coating film in the technical field of environmental protection materials, and specifically relates to a degradable polyurethane film and a preparation method thereof. Background Art

[0002] Currently, plastic coating films (such as polyethylene PE films) are widely used in fields such as food packaging and agricultural mulch films due to their low cost and excellent barrier properties. However, traditional plastics are difficult to degrade in the natural environment, and long-term accumulation leads to serious "white pollution". According to statistics in the journal Science, approximately 8 million tons of plastic waste enter the ocean globally every year, and packaging materials account for more than 40%. To replace traditional plastics, degradable materials have become a research hotspot. However, the existing technologies still have the following key defects: the limitations of existing degradable coating films and their susceptibility to environmental temperature and humidity. PLA (polylactic acid)-based coating films: Although they have biodegradability, their high brittleness, high cost (about 2-3 times that of PE films), and difficult processing limit large-scale applications; starch-based coating films, although they have a wide range of raw material sources and excellent degradation properties, have extremely low mechanical strength (tensile strength < 5 MPa) for pure starch films, insufficient mechanical strength, and are difficult to meet the puncture resistance requirements of packaging materials and have poor moisture resistance. The hydrogen bond interaction between ordinary starch and polyurethane molecules is weak, and phase separation easily occurs after blending, resulting in increased brittleness of the film material. High starch content can accelerate degradation but will significantly reduce mechanical strength; cellulose-based coating films, although they have good mechanical properties, their high crystallinity and hydrophobicity lead to poor compatibility with the polymer matrix, and the composite film is prone to delamination, and the degradation rate is significantly affected by environmental humidity. Polyurethane (PU) is used in the development of polyurethane films due to its good film-forming properties, but its high hydrophilicity results in low wet strength of the film material (the tensile strength decreases by > 50% after soaking), and the degradation rate of pure polyurethane films is uncontrollable. Existing studies have tried to improve the mechanical properties of starch-based films by adding plasticizers or inorganic nanoparticles, but there are generally problems such as easy migration and precipitation of plasticizers, resulting in poor long-term stability. Summary of the Invention

[0003] Aiming at the technical problems of the incompatible mechanical properties and degradation properties and poor moisture resistance of the coating films in the existing technology, the present invention first provides a degradable polyurethane film, which comprises the following components in parts by mass: 7.5-11 parts of polyurethane, 78-85 parts of water, 2.4-4.5 parts of hydroxyethyl starch, 1.3-2.5 parts of methyl cellulose, 1.6-3.2 parts of tributyl acetylcitrate, 0.85-1.3 parts of plasticizer, 0.1-0.16 parts of crosslinking agent, and 0.5-1.6 parts of reinforcing agent.

[0004] As a preference of the present invention, a hydrophobic coating is coated on the surface of the polyurethane film to improve its moisture resistance, and the thickness of the hydrophobic coating is 1-5 μm.

[0005] As a preference of the present invention, the plasticizer is two or more of dioctyl adipate, tricresyl phosphate, glycerol, sorbitol or polyethylene glycol; the crosslinking agent is at least one of sodium citrate and glutaraldehyde; the reinforcing agent is polymer hollow nanospheres.

[0006] As a preference of the present invention, the hydrophobic coating is a 5wt% poly(lactic acid) acetone solution.

[0007] As a preference of the present invention, the molecular weight of the hydroxyethyl starch is 200 kDa, and the viscosity of the methyl cellulose is 100 - 400 mPa·s (2% aqueous solution, 20 °C).

[0008] Secondly, the present invention also provides a method for preparing the above-mentioned polyurethane film, which includes the following steps:

[0009] ((1) Add polyurethane to deionized water and stir until completely dissolved to obtain a polyurethane glue solution;

[0010] (2) Sequentially add hydroxyethyl starch, methyl cellulose, tributyl acetyl citrate, plasticizer, and crosslinking agent to the polyurethane glue solution obtained in step (1), stir evenly to obtain a mixed solution;

[0011] (3) Add the reinforcing agent to the mixed solution obtained in step (2), stir evenly, and then subject it to repeated freeze-thaw to prepare a homogeneous composite glue solution;

[0012] (4) Coat the homogeneous composite glue solution obtained in step (3) on a release paper, dry it and then peel it off to form a composite film. Coat a hydrophobic coating on the surface of the composite film and cure it to obtain the target product.

[0013] As a preference of the present invention, the stirring temperature in step (2) is 55 °C and the stirring time is 3 h.

[0014] As a preference of the present invention, the stirring time in step (3) is 1 - 3 h and the number of freeze-thaw cycles is 3 - 5 times.

[0015] As a preference of the present invention, the drying temperature in step (4) is 70 - 85 °C and the drying time is 1 h; the curing temperature is 60 - 70 °C and the curing time is 30 - 50 min.

[0016] Advantages of the present invention:

[0017] 1. In the present invention, by using the easily degradable material hydroxyethyl starch to replace part of the polyurethane, the hydroxyethyl in the hydroxyethyl starch forms hydrogen bonds with the hydroxyl groups of the polyurethane, and the hydrophobic chain segments of the methyl cellulose fill the molecular gaps. The combination of the three increases the tensile strength to 10 MPa (30% - 50% higher than that of a single polyurethane film), and the degradation efficiency of the coating film can be regulated within a certain range by adjusting the ratio.

[0018] 2. The present invention changes the porosity, density and mechanical strength of the coating film material through a freeze-thaw cycle process at -40°C to 20°C, enhances the structural strength between materials, and simulates the performance under extreme environments.

[0019] 3. The surface of the polyurethane film of the present invention is coated with a hydrophobic coating so that the water contact angle ≥ 100°, and the moisture barrier property is increased to several times that of the commercially available polyurethane film, and it can be applied in a high-humidity environment.

[0020] 4. The present invention further improves the air permeability of the polyurethane film while lightening it by adding polymer hollow nanospheres as a reinforcing agent to the components of the polyurethane film. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic structural diagram of the polyurethane film of the present invention, in the figure: 1 - hydrophobic layer, 2 - inner coating layer. SPECIFIC IMPLEMENTATION METHODS

[0023] The technical solution of the present invention will be further specifically described below through examples.

[0024] Example 1

[0025] A degradable polyurethane film, comprising the following components in parts by weight: 8.9 parts of polyurethane, 80 parts of water, 4.5 parts of hydroxyethyl starch, 1.5 parts of methyl cellulose, 3 parts of tributyl acetylcitrate, 0.89 part of plasticizer, 0.15 part of crosslinking agent, and 1.2 parts of reinforcing agent.

[0026] The preparation method of the above polyurethane film is as follows:

[0027] (1) Preparation of polyurethane glue solution: Add 60 g of polyurethane to 540 g of deionized water at a temperature of 80°C, stir until completely dissolved, and prepare a polyurethane glue solution;

[0028] (2) Mixed modification: Add 30 g of hydroxyethyl starch, 10 g of methyl cellulose, 20 g of tributyl acetylcitrate, 5 g of glycerol, 1 g of dioctyl adipate and 1 g of sodium citrate to the polyurethane glue solution in sequence, stir at a constant temperature of 55°C for 3 h, then add 8 g of polymer hollow nanospheres and continue to stir for 3 h, and freeze-thaw repeatedly at -40°C to 20°C for 3 times to obtain a homogeneous composite glue solution;

[0029] (3) Coating and film formation: Coat the glue solution on the release paper through a coating roller, dry at 80°C for 1 h and then peel off to obtain a composite film with a thickness of about 61 μm;

[0030] (4) Hydrophobic coating treatment: Dissolve polylactic acid in acetone (concentration 5 wt%), spray it on the film surface to form a 5-μm-thick coating, and cure at 60°C for 30 min.

[0031] (5) Adjust the winding of the film through the tension control system.

[0032] Example 2

[0033] A degradable polyurethane film, comprising the following components in parts by weight: 11.2 parts of polyurethane, 78.4 parts of water, 3.68 parts of hydroxyethyl starch, 1.77 parts of methyl cellulose, 2.4 parts of tributyl acetylcitrate, 1.28 parts of plasticizer, 0.16 parts of crosslinking agent, 0.96 parts of reinforcing agent.

[0034] The preparation method of the above polyurethane film is as follows:

[0035] (1) Preparation of polyurethane glue solution: Add 70 g of polyurethane to 490 g of deionized water at 80 °C, stir until completely dissolved, and prepare a polyurethane glue solution;

[0036] (2) Mixed modification: Sequentially add 23 g of hydroxyethyl starch, 12 g of methyl cellulose, 15 g of tributyl acetylcitrate, 6 g of glycerol, 2 g of tricresyl phosphate, and 1 g of glutaraldehyde to the polyurethane glue solution, stir at a constant temperature of 55 °C for 3 h, then add 6 g of polymer hollow nanospheres and continue to stir for 2 h, and freeze-thaw repeatedly 4 times from -40 °C to 20 °C to obtain a homogeneous composite glue solution;

[0037] (3) Coating and film formation: Coat the glue solution on the release paper through a coating roller, dry at 80 °C for 1 h and then peel off to obtain a composite film with a thickness of about 81 μm;

[0038] (4) Hydrophobic coating treatment: Dissolve polylactic acid in acetone (concentration 5 wt%), spray it on the film surface to form a 3-μm-thick coating, and cure at 60 °C for 30 min.

[0039] (5) Adjust the winding of the film through the tension control system.

[0040] Example 3

[0041] A degradable polyurethane film, comprising the following components in parts by weight: 7.7 parts of polyurethane, 85.2 parts of water, 2.5 parts of hydroxyethyl starch, 1.3 parts of methyl cellulose, 1.65 parts of tributyl acetylcitrate, 0.88 parts of plasticizer, 0.11 parts of crosslinking agent, 0.55 parts of reinforcing agent.

[0042] The preparation method of the above polyurethane film is as follows:

[0043] (1) Preparation of polyurethane glue solution: Add 70 g of polyurethane to 770 g of deionized water at 80 °C, stir until completely dissolved, and prepare a polyurethane glue solution;

[0044] (2) Hybrid modification: 23 g of hydroxyethyl starch, 12 g of methyl cellulose, 15 g of tributyl acetylcitrate, 6 g of glycerol, 2 g of tricresyl phosphate, and 1 g of glutaraldehyde were successively added to the polyurethane glue solution, and stirred at a constant temperature of 55 °C for 3 h. Then, 5 g of polymer hollow nanospheres were added and stirred for another 1 h, and repeatedly frozen and thawed 5 times between -40 °C and 20 °C to obtain a homogeneous composite glue solution;

[0045] (3) Coating and film formation: The glue solution was coated on the release paper through a coating roller, dried at 80 °C for 1 h and then peeled off to obtain a composite film with a thickness of about 93 μm;

[0046] (4) Hydrophobic coating treatment: Poly(lactic acid) was dissolved in acetone (concentration 5 wt%), sprayed on the film surface to form a 3-μm-thick coating, and cured at 60 °C for 30 min.

[0047] (5) Adjust the winding of the film through the tension control system.

[0048] Example 4

[0049] A degradable polyurethane film, comprising the following components in parts by weight: 8.1 parts of polyurethane, 80.9 parts of water, 2.4 parts of hydroxyethyl starch, 2.4 parts of methyl cellulose, 3.2 parts of tributyl acetylcitrate, 1.1 parts of plasticizer, 0.16 parts of crosslinking agent, and 1.6 parts of reinforcing agent.

[0050] The preparation method of the above polyurethane film is as follows:

[0051] (1) Preparation of polyurethane glue solution: 50 g of polyurethane was added to 500 g of deionized water at a temperature of 80 °C and stirred until completely dissolved to prepare a polyurethane glue solution;

[0052] (2) Hybrid modification: 15 g of hydroxyethyl starch, 15 g of methyl cellulose, 20 g of tributyl acetylcitrate, 4 g of glycerol, 2 g of tricresyl phosphate, 1 g of polyethylene glycol, and 1 g of glutaraldehyde were successively added to the polyurethane glue solution, and stirred at a constant temperature of 55 °C for 3 h. Then, 10 g of polymer hollow nanospheres were added and stirred for another 1 h, and repeatedly frozen and thawed 5 times between -40 °C and 20 °C to obtain a homogeneous composite glue solution;

[0053] (3) Coating and film formation: The glue solution was coated on the release paper through a coating roller, dried at 80 °C for 1 h and then peeled off to obtain a composite film with a thickness of about 68 μm;

[0054] (4) Hydrophobic coating treatment: Poly(lactic acid) was dissolved in acetone (concentration 5 wt%), sprayed on the film surface to form a 1-μm-thick coating, and cured at 60 °C for 30 min.

[0055] (5) Adjust the winding of the film through the tension control system.

[0056] Example 5

[0057] A degradable polyurethane film, comprising the following components in parts by weight: 8.1 parts of polyurethane, 81 parts of water, 2.4 parts of hydroxyethyl starch, 2.4 parts of methyl cellulose, 3.2 parts of tributyl acetylcitrate, 0.81 part of plasticizer, 0.32 part of crosslinking agent, and 1.6 parts of reinforcing agent.

[0058] The preparation method of the above polyurethane film is as follows:

[0059] (1) Preparation of polyurethane glue solution: Add 50 g of polyurethane to 500 g of deionized water at 80 °C, stir until completely dissolved, and prepare a polyurethane glue solution;

[0060] (2) Mixed modification: Sequentially add 15 g of hydroxyethyl starch, 15 g of methyl cellulose, 20 g of tributyl acetylcitrate, 4 g of glycerol, 1 g of polyethylene glycol, and 2 g of glutaraldehyde to the polyurethane glue solution, stir at a constant temperature of 55 °C for 3 h, then add 10 g of polymer hollow nanospheres and continue to stir for 2 h, and freeze-thaw repeatedly 4 times from -40 °C to 20 °C to obtain a homogeneous composite glue solution;

[0061] (3) Coating and film formation: Coat the glue solution on the release paper through a coating roller, dry at 80 °C for 1 h and then peel off to obtain a composite film with a thickness of about 68 μm;

[0062] (4) Hydrophobic coating treatment: Dissolve polylactic acid in acetone (concentration 5 wt%), spray it on the film surface to form a 1-μm-thick coating, and cure at 60 °C for 30 min.

[0063] (5) Adjust the winding of the film through a tension control system.

[0064] Tensile strength test

[0065] Table 1 Mechanical property test evaluation table

[0066]

[0067] According to the results in Table 1, it can be seen that compared with the commercially available polyurethane film, the degradable polyurethane film prepared in this application has been greatly improved in mechanical properties.

[0068] Water resistance test

[0069] Referring to the ASTM D7334 standard, a contact angle measuring instrument (such as DataPhysics OCA20) is used to measure the static contact angle of deionized water on the coating surface.

[0070] Table 2 Hydrophobic property test evaluation table

[0071]

[0072] According to the results in Table 2, in this application, a porous structure of the film layer is constructed through a freeze-thaw process (4 cycles of -40°C to 20°C). Combining with the low surface energy characteristics of the polylactic acid coating, the moisture barrier property of the coated film is increased several times that of the commercially available polyurethane film while maintaining a tensile strength ≥ 10 MPa.

[0073] Degradation test

[0074] Table 3 Degradation performance test evaluation table

[0075]

[0076]

[0077] The weight loss rate of the control group was 73.6% after 60 days in the natural environment, while the weight loss rate of Example 1 under the same conditions was 93.2%, far exceeding that of the control group. This is attributed to the biodegradation priority of hydroxyethyl starch: the starch part degrades rapidly to form a porous structure, but the cellulose / polyurethane skeleton delays the overall disintegration. Example 2 under the high temperature and high humidity environment (industrial composting) had a weight loss rate of 96.5% within 45 days because the high composting temperature (35°C) accelerated microbial metabolism, and the polylactic acid coating hydrolyzed rapidly under this condition. Example 4 under the low temperature and low humidity environment (room temperature drying) only lost 32.3% of its weight in 180 days, indicating that the dry environment significantly inhibited degradation, which conforms to the "controllable degradation" characteristic of this application and meets the long-term storage requirements. Thick coating (Example 1, 5 μm): The highest weight loss rate (93.2%) because the thicker coating delayed water penetration, resulting in slower initial degradation, but later microbial erosion dominated the degradation. Thin coating (Example 4, 1 μm): The lowest weight loss rate (42.3%) because the too-thin coating could not effectively block moisture, but the internal pores constructed by the freeze-thaw process in this application accelerated local degradation.

[0078] The above examples are only relatively representative examples of the present invention. The specific implementation cases are only used to exemplarily illustrate the technical implementation path of the present invention. Those skilled in the art can make adaptive adjustments to the material system, interface treatment process, etc. without departing from the core technical features defined in the claims. Such technical deformations, whether manifested as material substitution, structural reorganization or application scenario migration, as long as their technical effects are directly related to the innovation points described in the specification of the present invention, belong to the reasonable extension scope of the patent claim of the present invention.

Claims

1. A degradable polyurethane film, characterized in that, The invention comprises the following components in parts by weight: 7.5-11 parts of polyurethane, 78-85 parts of water, 2.4-4.5 parts of hydroxyethyl starch, 1.3-2.5 parts of methyl cellulose, 16.-3.2 parts of acetyl tributyl citrate, 0.85-1.3 parts of plasticizer, 0.1-0.16 parts of crosslinking agent and 0.5-1.6 parts of reinforcing agent.

2. The polyurethane film according to claim 1, characterized in that, The surface of the polyurethane film is coated with a hydrophobic coating, wherein the thickness of the hydrophobic coating is 1 to 5 μm.

3. The polyurethane film according to claim 2, characterized in that, The hydrophobic coating is a 5 wt% polylactic acid acetone solution.

4. The polyurethane film according to claim 1, characterized in that, The plasticizer is two or more of dioctyl adipate, tricresyl phosphate, glycerol, sorbitol or polyethylene glycol; the crosslinking agent is at least one of sodium citrate and glutaraldehyde; and the reinforcing agent is polymer hollow nanospheres.

5. The polyurethane film according to claim 1, characterized in that The molecular weight of the hydroxyethyl starch is 200 kDa, and the viscosity of the methyl cellulose is 100-400 mPa·s (2% aqueous solution, 20° C.).

6. The preparation method of the polyurethane film according to any one of claims 1 to 5, characterized in that, The following steps are involved: (1) Adding polyurethane to deionized water and stirring until completely dissolved to obtain polyurethane glue; (2) adding hydroxyethyl starch, methyl cellulose, acetyl tributyl citrate, a plasticizer, and a cross-linking agent to the polyurethane glue obtained in step (1) in sequence and stirring evenly to obtain a mixed solution; (3) the reinforcing agent in the mixed solution obtained in step (2) is stirred evenly and then repeatedly frozen and thawed to obtain a homogeneous composite glue solution; (4) The homogeneous composite adhesive obtained in step (3) is coated on a release paper and peeled off after drying to form a composite film. A hydrophobic coating is applied on the surface of the composite film and cured to obtain the target product.

7. The preparation method according to claim 6, characterized in that In step (2), the stirring temperature is 50° C. to 70° C., and the stirring time is 1 to 4 h.

8. The preparation method according to claim 6, characterized in that, The stirring time in step (3) is 1 to 3 hours, and the number of freeze-thaw cycles is 3 to 5 times.

9. The preparation method according to claim 6, wherein In step (4), the drying temperature is 70-85° C. and the drying time is 1 h.

10. The preparation method according to claim 6, characterized in that, In step (4), the curing temperature is 60-70° C. and the curing time is 30-50 min.

Citation Information

Patent Citations

  • Starch-polyurethane blend garment bag and production method thereof

    CN106243682A

  • High-toughness plastic film

    CN108586930A

  • Degradable packaging bag and preparation method thereof

    CN108929465A

  • Strippable protective film and preparation method thereof

    CN110615957A